414 Immunoreactivity of Polymerized and Digested Beta-lactoglobulin to IgE from Milk Allergic Patients - Villas-Boas, Mariana Battaglin (World Allergy Organization Journal, 2012)
BACKGROUND: Beta-lactoglubulin (β-Lg), is one of the most important allergens in bovine milk. The allergenicity is mainly associated to its stable structure, resistant to heat and digestive processes. With the purpose of decreasing its allergenicity, some processes have been studied, including enzymatic treatments using transglutaminase (TG), an enzyme that catalyses the formation of inter and intramolecular isopeptide bonds between glutamine and lysine residues which could alters both the structure and antigenic sites in the protein. The allergenicity of β-Lg hydrolysates obtained after a simulated gastrointestinal digestion (GI) and previously polymerized by TG enzyme was studied. METHODS: The β-Lg (7% w/v), donated by Davisco Inc., was modified by 2 different methods (1) heat treated (80°C/60 min) and polymerized by TG (10 U g(−1) protein), and (2) polymerized by TG in the presence of the reducing agent Cysteine - Cys (0.1 mol L(−1)). After modification the samples were submitted to in vitro digestion, simulating gastric and duodenal conditions (Moreno, 2005; Martos et al, 2010). The characterization of the samples was performed by electrophoresis (SDS-PAGE) and Reversed-phase high performance liquid chromatography (RP-HPLC). The allergenicity of the protein was measured by ELISA, using sera of milk allergic patients. RESULTS: The untreated β-Lg was resistant to pepsin while the samples polymerized by TG showed an increased in the susceptibility to pepsin, since a predominance of low molecular mass (MM) peptides, 3.0 to 6.0 kDa (by SDS-PAGE) and peptides with low hydrophilicity (by RP-HPLC) were detected. After duodenal digestion, the polymerized samples showed an increased in the intensity of the peaks with high hydrophilicity, indicating a potential susceptibility of polymerized β-Lg to GI digestion. Immunoreactivity to IgE from sera of allergic patients was retained for β-Lg polymerized after heat treatment, even after in vitro gastric digestion; while for the sample polymerized in presence of Cys it decreased considerably after pepsinolysis. After duodenal digestion, both polymerized samples showed an important decrease in the immunoreactivity response, compared to untreated β-Lg. CONCLUSIONS: These findings showed that the polymerization alters the susceptibility of β-Lg to GI digestion and could have implications in the allergenic characteristics of this protein.